Total acidity in petroleum: A Bibliometric analysis (Research, Society and Development, 2019)
The decline of conventional oil reserves leads to the exploitation of acid crudes. However, its acid components are of great concern to the industry due to its corrosivity and depreciated market value. The internationally accepted index that determines the acidity in crude oils is the total acid number (TAN), however, its reliability is questioned. In order to find out the most important papers and countries in this research field, a bibliometric analysis on petroleum acidity is presented. The database used for the bibliometric analysis was the Web of Science® (WoS). From the research results, a database of articles was built, and a great number of publications on characterization of naphthenic acids, determination of acidity and extraction of acidic compounds from petroleum was discovered. This indicates the relevance of the research on acid crudes, in addition, the frequent attempt to introduce new methods for its determination indicates that there is still a field of research to be explored.